Thermodynamic analysis of a novel integrated biomass pyrolysis-solid oxide fuel cells-combined heat and power system for co-generation of biochar and power - Kuo, Po-Chih; Illathukandy, Biju; Özdemir, Faruk; Woudstra, Theo; Aravind, P. V. (Frontiers in Energy Research, 2022)
Biochar derived from pyrolysis or gasification has been gaining significant attention in the recent years due to its potential wide applications for the development of negative emissions technologies. A new concept was developed for biochar and power co-generation system using a combination of biomass pyrolysis (BP) unit, solid oxide fuel cells (SOFCs), and a combined heat and power (CHP) system. A set of detailed experimental data of pyrolysis product yields was established in Aspen Plus to model the BP process. The impacts of various operating parameters including current density (j), fuel utilization factor (Uf), pyrolysis gas reforming temperature (Treformer), and biochar split ratio (Rbiochar) on the SOFC and overall system performances in terms of energy and exergy analyses were evaluated. The simulation results indicated that increasing the Uf, Treformer, and Rbiochar can favorably improve the performances of the BP-SOFC-CHP system. As a whole, the overall electrical, energy and exergy efficiencies of the BP-SOFC-CHP system were in the range of 8–14%, 76–78%, and 71–74%, respectively. From the viewpoint of energy balance, burning the reformed pyrolysis gas can supply enough energy demand for the process to achieve a stand-alone BP-SOFC-CHP plant. In case of a stand-alone system, the overall electrical, energy and exergy efficiencies were 5.4, 63.9 and 57.8%, respectively, with a biochar yield of 31.6%.